Contribuições e desafios do(a) pedagogo(a) na educação especial em dois centros de educação infantil em Parintins - AM - Beltrão, Nataly Teixeira (Brasil, 2025)
This research is called Contributions and challenges of the pedagogue in Special Education in two Early Childhood Education centers, in Parintins-AM. It aimed to understand and identify the contributions and challenges that these education professionals face daily to develop their work in early childhood education. The research was developed through a qualitative approach, as it seeks to explore and understand the "how" and "why" of phenomena, offering a deeper insight into issues that cannot be easily quantified. The epistemological approach to research is phenomenological, as it aims to understand the phenomenon being investigated. The results of the study are based mainly on field research and bibliographic sources. In the development we address topics on: challenges and contributions faced by pedagogues in special education; specialization of professionals for the service and quality of teaching for students with disabilities. The result of the research clearly shows the role of the pedagogue and the challenges in the development of the school, as these require changes in the posture, perception and organization of the educational system and inclusion policies.